Metamorfoses da cidade medieval. A coexistência entre a comunidade judaica e a catedral de Viseu - de Sousa Saraiva, Anísio Miguel (2012)
Viseu’s status as political, ecclesiastical and commercial centre acted as a factor of development and attraction of merchants and Jews. The first testimonies of the Hebraic presence in this city are from the late 13th century, whose commune prospered mainly from the early 15th century, at the time when Viseu  initiated a major process of rebuilt, after three decades of conflict and destruction which characterized the Ferdinand Reign and the first years of D. João I’s government.In this paper we will approach the multi confessional profile of medieval Viseu and the jewish contribution to the construction of its urban and social space, in the period prior to the hebraic expulsion, in 1496. We will analyze the outline of this coexistence and collaboration process, though not always peaceful, between jews and the cathedral. The latter, as owner of the vast majority of the urban property of the city, rolled as an important liaison between christians and the jewish minority and played a strong influence in their mechanisms of spatial organization. From certain issues analyzed in this extent, we will stand out the delocalization of the Jewish District mostly due to the consequences of the relations of power and of the defense of Jewish and Christian’s interests in the context of the reorganization of the 15th’s urban network of Viseu. Manuscript sources: Arquivo Distrital de Viseu (ADVIS) Scrolls, m. 00 (n. 4, 44, 58, 161, 185, 328, 337); m. 09 (n. 12, 14); m. 15 (n. 15, 46); m. 16 (n. 39); m. 18 (n. 09, 72, 76, 109); m. 19 (n. 19 verso, 79); m. 20 (n. 91); m. 21 (n. 74); m. 22 (n. 04, 20); m. 23 (n. 49, 67); m. 25 (n. 18b); m. 26 (n. 16); m. 28 (n. 55); m. 30 (n. 10); m. 32 (n. 22, 37); m. 33 (n. 07, 08, 26, 44); m. 34 (n. 06, 44); m. 35 (n. 17, 26, 27, 45b); m. 36 (n. 50); m. 37 (n. 04); m. 38 (n. 36a, 50); m. 39 (n. 06, 12, 15); m. 40 (n. 31); m. 41 (n. 11, 32); m. 42 (n. 03); m. 43 (n. 06, 24, 32, 33, 35, 46); m. 44 (n. 14, 18, 24, 31); m. 46 (n. 14, 35); m. 47 (n. 18, 19, 29, 35); m. 48 (n. 07, 36, 47, 48, 50); m. 49 (n. 11, 12, 15, 17, 63); m. 50 (n. 31, 81). Arquivo Nacional da Torre do Tombo (ANTT) Leitura Nova, Beira, Liv. 2. Sé de Viseu, Documentos Régios, m. 1 (n. 23). Fontes impressas: Chancelarias Portuguesas: D. Afonso IV. Org. A. H. de Oliveira Marques, vol. 2. Lisboa: INIC-CEH/UNL, 1990. Chancelarias Portuguesas: D. Duarte. Vol. 1, Tomo 1. Org. João José Alves Dias. Lisboa: CEH-UNL, 1998. Chancelarias Portuguesas: D. João I. Vol. 1, T. 1. Org. João José Alves Dias. Lisboa: CEH-UNL, 2004.   Bibliography: ANDRADE, Amélia Aguiar – O desaparecimento espacial das judiarias nos núcleos urbanos portugueses de finais da Idade Média: o caso de Lisboa. In Estudos de Homenagem ao Prof. Doutor José Marques. Vol. 1. Porto: Faculdade de Letras, 2006, p. 143-163. ANTUNES, José – Acerca da liberdade de religião na Idade Média: mouros e judeus perante um problema teológico-canónico. Revista de História das Ideias. 11 (1989) 63-84. ATLAS de cidades medievais portuguesas: séculos XII-XV. Vol. 1. Lisboa: INIC, 1990. BALLESTEROS, C. – A judiaria e a sinagoga medieval de Évora. In Os judeus sefarditas entre Portugal, Espanha e Marrocos. Lisboa: Colibri, 2004, p. 191-218. BARROS, Henrique da Gama – Comunas de Judeus e comunas de mouros em Portugal em tempos passados. Revista Lusitana. 34 (1936) 259-260. BEIRANTE, Maria Ângela – As mancebias nas cidades medievais portuguesas. In O ar da cidade: ensaios de história medieval e moderna. Lisboa: Ed. Colibri, 2008, p. 7-24. BEIRANTE, Maria Ângela – Espaços públicos nas cidades portuguesas medievais: Santarém e Évora. In O ar da cidade. Ensaios de História Medieval e Moderna. Lisboa: Ed. Colibri, 2008, p. 182-183. BEIRANTE, Maria Ângela – Évora na Idade Média. Lisboa: FCG/JNICT, 1995. CASTILHO, Liliana Andrade – O centro histórico de Viseu. Beira Alta. 63-3/4 (2004) 330-336. CHORÃO, J. – Islão e cristianismo: entre a tolerância e a guerra santa. In História Religiosa de Portugal. Vol. 1: Formação e Limites da Cristandade. Rio de Mouro: Círculo de Leitores, 2000, p. 102-116. COELHO, Maria Helena da Cruz – O concelho e senhorio de Viseu em Cortes. In Actas do congresso infante D. Henrique, Viseu e os Descobrimentos. Viseu: Câmara Municipal, 1995, p. 93 e 102. CORDEIRO, Maria Teresa Gomes – Adonai nos cárceres da Inquisição – os cristãos-novos de Viseu quinhentista. Viseu: Arqueohoje/Projecto Património, 2010. CORDEIRO, Maria Teresa Gomes – Cristãos-novos, a raia e o êxodo para Castela: a entrada da Inquisição em Viseu (1637). Guarda: Centro de Estudos Ibéricos, 2007. DIAS, Geraldo Coelho – Presença de judeus no Porto: da Idade Média à Modernidade. In Os reinos ibéricos na Idade Média. Vol. 1. Porto: Livraria Civilização, 2003, p. 424-440. GASPAR, Jorge – A cidade portuguesa na Idade Média: aspectos da estrutura física e desenvolvimento funcional. In La ciudad hispanica durante los siglos XIII al XVI. Actas do colóquio. Madrid: Universidad Complutense, 1982, p. 134-136. GOMES, Rita Costa – Um microcosmos citadino: a judiaria medieval da Guarda. In Guarda, história e cultura judaica. Guarda: Museu, 2000. GOMES, Saul – A comuna judaica de Leiria das origens à expulsão: introdução ao seu estudo histórico e documental. Lisboa: Cátedra de Estudos Sefarditas «Alberto Benveniste», 2010. GOMES, Saul – A comunidade judaica de Coimbra medieval. Coimbra: INATEL, 2003. GOMES, Saul – A mouraria de Leiria: problemas sobre a presença moura no centro do país. Estudos Orientais. 2 (1991) 155-177. GOMES, Saul – Ser-se judeu na Coimbra medieval. In Minorias étnicas e religiosas em Portugal: história e actividade. Actas do Curso de Inverno. Coimbra: [s.n.], 2003, p. 61-82. GONÇALVES, Iria – Para o estudo da área de influência do Porto nos fins do século XIV. In Um olhar sobre a cidade medieval. Cascais: Patrimonia, 1996, p. 139-152. IZQUIERDO BENITO, Ricardo – Los conflitos sócio-religiosos en las ciudades medievales castellanas. In La conviencia en las ciudades medievales. Nájera. Encuentros Internacionales del Medievo 2007. Logroño: Instituto de Estudios Riojanos, 2008, p. 84-100. LÓPEZ BELTRÁN, María Teresa – La prostitución en el reino de Granada a finales de la Edad Media. Málaga: Centro de Ediciones de la Diputación, 2003. MAGALHÃES, Joaquim Romero de – Os cristãos-novos: da integração à segregação. In História de Portugal. Dir. José Mattoso, vol. 3. Rio de Mouro: Círculo de Leitores, 1993, p. 475-476. MARQUES, A. H. de Oliveira – A constituição de um condado. In Nova História de Portugal. Dir. Joel Serrão e A. H. de Oliveira Marques. Vol. 3: Portugal em definição de fronteiras (1096-1325). Coord. Maria Helena Coelho e Armando Carvalho Homem. Lisboa: Ed. Presença, 1996, p. 11-23. MARQUES, A. H. de Oliveira – Introdução à história da cidade medieval portuguesa. In Novos ensaios de história medieval portuguesa. Lisboa: Presença, 1988, p. 13-42. MARQUES, A. H. de Oliveira – O surto urbano, a moeda e os preços. In Nova História de Portugal. Dir. Joel Serrão e A. H. de Oliveira Marques. Vol. IV: Portugal na Crise dos Séculos XIV e XV. Lisboa: Presença, 1987, p. 187-190. MARQUES, José – A contenda do cabido com os judeus de Braga, na segunda metade do século XV. Revista Altitude. 4 (1981) 29-32. MARQUES, José – As judiarias de Braga e de Guimarães no século XV. In Xudeus e Conversos na Historia. Congreso Internacional, Ribadavia, 1991. Vol. 2. Santiago de Compostela: Editorial de la Historia, 1994, p. 351-363. MATTOSO, José – Dois séculos de vicissitudes políticas. In História de Portugal. Dir. José Mattoso. Vol. 2: A monarquia feudal (1096-1480). Rio de Mouro: Círculo de Leitores, 1992, p. 23-64. MATTOSO, José – Os concelhos. In História de Portugal. Vol. II: A monarquia feudal (1096-1480). Dir. José Mattoso. Rio de Mouro: Círculo de Leitores, 1992, p. 207-211. MOLINA MOLINA, Ángel Luis – La prostitución en la Castilla bajomedieval. Clio & Crimen. 5 (2008) 138-150. MOLINA MOLINA, Ángel Luis – Mujeres públicas, mujeres secretas: la prostitución y su mundo (siglos XIII-XVII). Murcia: Editorial KR, 1998. MONTEIRO, Isabel – A judiaria de Viseu. Monumentos. 13 (2000) 57-61. MONTEIRO, Isabel – Os judeus na região de Viseu. Viseu: RTDL, 1997. MONTEIRO, Isabel – Viseu a identidade histórica: o próximo como o “outro”. VISEU.M. 1 (2008) 142-163. MORENO, Humberto Baquero – Movimentos sociais antijudaicos em Portugal no século XV. In Marginalidade e conflitos sociais em Portugal nos séculos XIV e XV. Estudos de História. Lisboa: Ed. Presença, 1985, p. 79-88. MORENO, Humberto Baquero – Reflexos na cidade do Porto da entrada dos conversos em Portugal nos fins do século XV. In Marginalidade e conflitos sociais em Portugal nos séculos XIV e XV. Estudos de História. Lisboa: Ed. Presença, 1985, p. 133-160. MOUTA, J. Henriques – Panorâmica e dinâmica de Viseu medieval. I: Toponímia. Beira Alta. 27-2 (1968) 281-300. NERY, António de Seixas – O cabido de Viseu nos inícios da Idade Moderna, senhorio e rendas (1400-1500). Porto: FLUP, 1996 (Tese de Mestrado). RIBEIRO, Maria do Carmo Franco – Braga entre a época romana e a Idade Moderna: uma metodologia de análise para a leitura da evolução da paisagem urbana. Braga: Universidade do Minho, 2008 (Tese de Doutoramento). SARAIVA, Anísio Miguel de Sousa – A cidade de Viseu no rasto da guerra: dos conflitos fernandinos à paz definitiva com Castela. In A Guerra e a Sociedade na Idade Média. Actas das VI Jornadas Luso-Espanholas de Estudos Medievais (2008). Vol. 1. [Torres Novas]: SPEM, 2009, p. 323-358. SARAIVA, Anísio Miguel de Sousa – A inserção urbana das catedrais medievais portuguesas: o caso da catedral de Lamego. In Catedral y ciudad medieval en la Península Ibérica. Eds. Eduardo Carrero y Daniel Rico. Múrcia: Nausícaä, 2004, p. 243-245. TAVARES, Maria José Ferro – O difícil diálogo entre judaísmo e cristianismo. In História Religiosa de Portugal. Dir. Carlos Moreira Azevedo. Vol. 1: Formação e limites da cristandade. Coord. Ana Maria Jorge e Ana Maria Rodrigues. Rio de Mouro: Círculo de Leitores, 2000, p. 53-54. TAVARES, Maria José Ferro – Os judeus em Portugal no século XIV. Lisboa: Guimarães Ed., 1979. TAVARES, Maria José Ferro – Os judeus em Portugal no século XV. 2 vols. Lisboa: UNL-INIC, 1982-1984. TAVARES, Maria José Ferro – Os judeus na Beira Interior. In Guarda, história e cultura judaica. Guarda: Museu, 2000. TAVARES, Maria José Ferro – Pobres, minorias e marginais: localização no espaço urbano. In A Cidade. Jornadas inter e pluridisciplinares. Vol. 1. Lisboa: Universidade Aberta, 1993, p. 141-153. TAVARES, Maria José Ferro – Revoltas contra os judeus no Portugal medieval. Revista de História das Ideias. 6 (1984) 165-167. TRINDADE, Luísa – Jewish communities in portuguese late medieval cities: space and identity. In Religion, ritual and mythology: aspects of identity formation in Europe. Pisa: University Press, 2006, p. 68-73. TRINDADE, Luísa – Urbanismo na composição de Portugal. Coimbra: FLUC, 2009 (Tese de Doutoramento). VENTURA, Leontina – D. Afonso III. Rio de Mouro: Círculo de Leitores, 2006. VENTURA, Margarida Garcez – Contributo para uma leitura social do espaço na Lisboa quatrocentista: o debate sobre a localização das judiarias. Revista Portuguesa de História. 36-1 (2002/2003) 229-240.